Judas, the disciple who was known to the high priest: A deconstruction of the betrayal based on John 18:15 - Chatelion Counet, Patrick (HTS teologiese studies, 2011)
After his arrest, Jesus is taken to the high priest. According to John 18:15 he is accompanied by ‘another disciple’. In this article, I discuss the possibility that this other disciple was Judas. He is the one who was known to the high priest. The arguments to put him in this position are derived from a narrative analysis of the Gospel. What is the actantial role of Judas in the Gospel? Tradition describes him as an opponent of Jesus. Against this, one can see him as a helper who supports Jesus’ intention to convince the high priest and the Sanhedrin of his divine mission. In the group of Jesus Judas carries the purse. The text of the Gospel uses a curious Greek word (almost a hapax legoumenon), glôssokomon, for ‘purse’. In the Septuagint, this word indicates the Ark of the Covenant. It is highly significant for the role of Judas. It shows that the text of the Gospel sometimes generates meanings that the author cannot control.